Frische Katfische werden aufgeschnitten ehe sie zum Trocknen ausgelegt werden, John Gear in Okak 1913 - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of John Gear at Okak mission station splitting fresh codfish so it can be laid out for drying, 1913. A young Inuit boy is standing to the left of Gear. Photograph of John Gear at Okak mission station splitting fresh codfish so it can be laid out for drying, 1913. A young Inuit boy is standing to the left of Gear.